Assessment of Environmental Issues in Marginalized Populations: Study Case of Educational Institution in the Department of Santander, Colombia - Castro Camargo, Leidy Andrea; George Bracho, Sharon Beatriz; Riatiga Fandiño, Hugo; Vera Mercado, Erik José; Castro Molano, Liliana del Pilar (Ingeniería Solidaria, 2016)
Introduction: this article was produced by the research project “Assessment of the environmental situation in educational institutions” developed in 2015 by the Industrial University of Santander and the University of Santander. The addressed research problem derives from the hurdle that current educational institutions must overcome when working with marginalized populations in creating environmental awareness and visualizing a future with sustainable educational institutions.Methodology: in order to perform the Environmental Impact Assessment (eia) in the case study educational institution, the conesa method and the measurement of the “ecological footprint” were applied. The resulting information was analyzed so that the educational institution would alleviate the environmental effects of daily actions of students, teachers and staff during the general course of operations.Results: a significant impact of social and cultural variables was made in the environment. Given the aforementioned, the findings indicated the need to promote good citizenship behaviors through play-like strategies that would allow the students to build social guidelines and create symbols associated with environmental conservation.Conclusion: the environmental perception of the case study educational institution was assessed through a statistical analysis that produced an unfavorable environmental perception. The biggest impact identified is associated to a high consumption of water, followed by the impact associated with high level noise.
Keywords: environmental; evaluation; ecological footprint; impact; perception; sustainability